Climate and genotype influences on carbon fluxes and partitioning in Eucalyptus plantations - Campoe, Otávio C. [UNESP]; Alvares, Clayton A. [UNESP]; Carneiro, Rafaela L.; Binkley, Dan; Ryan, Michael G.; Hubbard, Robert M.; Stahl, James; Moreira, Gabriela; Moraes, Luiz Fabiano; Stape, José Luiz [UNESP] (Elsevier, 2020)
Clonal plantations of Eucalyptus are among the most productive forests in the world, with intensification of silviculture and genetic breeding doubling the wood mean annual increments over the past four decades. The TECHS Project demonstrated that even with intensive silviculture, wood production varies by more than two-fold across environmental gradients, and growth of highly selected clones differs by more than two-fold within a site. Wood production accounts for less than half of the photosynthesis of a forest, and we tested two hypotheses about the relation between wood production and the entire carbon balance for five genotypes across four of the TECHS sites, varying in temperature and water availability. We hypothesized that the influence of the environment on carbon fluxes and partitioning related to gross primary production would be consistent across genotypes. We also hypothesized that carbon flux and partitioning would be more sensitive to water stress than temperature. Annual average temperatures ranged from 18 to 27 °C, and annual rainfall ranged from about 600 to 1500 mm yr−1. Water stress was further tested by reduction in rainfall within sites using troughs to capture about 30% of incoming rain. The geographic gradient led to a six-fold range in wood net primary production during the two years of measurement (from age 1.5 to 3.5 years, the period of maximum current annual increment). Gross primary production (GPP) differed only by two-fold, highlighting very large differences among sites in partitioning: wood net primary production (NPP) accounted for 44% of GPP on sites with higher GPP, and only 34% of GPP on lower GPP sites. The average differences for wood NPP among clones was also large, with about half of the differences among clones relating to differences in GPP, and half to differences in the partitioning to wood NPP. The clones showed similar partitioning patterns across sites, supporting our first hypothesis. Differences across sites and clones in partitioning of GPP to wood NPP related inversely to belowground allocation. Belowground partitioning of carbon increased with increasing temperature and increasing water stress. Our second hypothesis was rejected, as patterns across sites related somewhat more strongly to temperature than to water stress. Overall, this ecophysiological investigation in the TECHS Project underscored the importance of understanding how carbon budgets differ across sites (even with intensive silviculture), and why clones can largely differ in wood production.
Keywords: Belowground allocation; Clonal plantation; Drought tolerant; Genotypes; Wood productivity; Zoning